High sensitivity tapered fiber refractive index biosensor using hollow gold nanoparticles - Parisa Borjikhani; Nosrat Granpayeh; Mohammad Ismail Zibaii (Scientific Reports)
Abstract A localized surface plasmon resonance (LSPR) sensor based on tapered optical fiber (TOF) using hollow gold nanoparticles (HAuNPs) for measuring the refractive index (RI) is presented. This optical fiber sensor is a good candidate for a label-free RI biosensor. In practical biosensors, bioreceptors are immobilized on nanoparticles (NPs) that only absorb specific biomolecules. The binding of these biomolecules to the receptors changes the local RI around the sensor and this change is detected by the transmittance spectrum of the fiber. Fast, accurate, easy and low-cost disease diagnosis are the advantages of optical fiber biosensors. In this paper, the structure theory is reviewed and the sensor is simulated by the finite difference time domain (FDTD) method and the finite element method (FEM) and the effect of the thickness and diameter of the HAuNPs and the waist diameter of the TOF is investigated. For the structure with HAuNPs thickness (2.5 nm), diameter (50 nm), and the fiber waist diameter of 10 μm, the wavelength sensitivity of 489.8 nm/RIU and full width at half maximum (FWHM) of 50 nm are obtained, which are better than those specifications in some other LSPR fiber sensors. In addition, the sensitivity of the sensor increases about 2–3 times compared to those of sensors with the same structure. Although there are many parameters in human blood that can change its RI, in practical work, the special bioreceptors on the sensor can deactivate other markers except the specific cancer markers, which changes the effective RI. Therefore, this optical fiber sensor is used for label-free detecting the RI of cancer cells and can be used as a biosensor for the detection of early stages of cancers in a non-invasive way, just using human blood samples.